In Vitro Evaluation of a Vibrating-Mesh Nebulizer Repeatedly Use over 28 Days - Hui-Ling Lin; Chi-Shuo Chen; James B. Fink; Guo-Hao Lee; Chun-Wei Huang; Jui-Chi Chen; Zi Yi Chiang (MDPI AG, 2020)
This in vitro study evaluates the performance of a disposable vibrating-mesh nebulizer when used for 28 days. A lung model was used to simulate the breathing pattern of an adult with chronic obstructive pulmonary disease. The vibrating-mesh nebulizer was used for three treatments/day over 28 days without cleaning after each test. Results showed that the inhaled drug dose was similar during four weeks of use (p = 0.157), with 16.73 ± 4.46% at baseline and 15.29 ± 2.45%, 16.21 ± 2.21%, 17.56 ± 1.98%, and 17.13 ± 1.81%, after the first, second, third, and fourth weeks, respectively. The particle size distribution, residual drug volume, and nebulization time remained similar across four weeks of use (p = 0.110, p = 0.763, and p = 0.573, respectively). Mesh was inspected using optical microscopy and showed that approximately 50% of mesh pores were obscured after 84 runs, and light penetration through the aperture plate was significantly reduced after the 21st use (p < 0.001) with no correlation to nebulizer performance. We conclude that the vibrating-mesh nebulizer delivered doses of salbutamol solution effectively over four weeks without cleaning after each use even though the patency and clarity of the aperture plate were reduced by the first week of use.